Interindividual variability in CYP3A‐mediated venetoclax metabolism in vitro and in vivo in patients with chronic lymphocytic leukemia - Jonghwa Lee; Jessica L. Beers; Isabel Cheng; Vivian Truong; Zachary Brown; Benyam Muluneh; Catherine C. Coombs; Klarissa D. Jackson (Clinical and Translational Science)
Abstract Venetoclax is a first‐in‐class orally administered B‐cell lymphoma‐2 inhibitor used to treat chronic lymphocytic leukemia (CLL). Venetoclax is primarily metabolized in the liver by cytochrome P450 (CYP) 3A4 to its major metabolite M27, via M5, and M2, M3, and M4 via oxidation. Although venetoclax is a breakthrough in CLL treatment, managing drug safety and toxicity remains a clinical challenge. The objectives of this study were to investigate how individual CYP3A activity and protein expression affect hepatic venetoclax metabolism in vitro and examine whether plasma 4β‐hydroxycholesterol (4β‐HC)/cholesterol ratio can predict venetoclax metabolism in vitro and in vivo. In human liver microsomes (n = 20) and primary human hepatocytes (n = 15), venetoclax metabolite formation varied widely between donors and significantly correlated with CYP3A activity (midazolam 1′‐hydroxylation) and CYP3A4 protein expression. Venetoclax metabolite formation positively correlated with 4β‐HC/cholesterol ratio in plasma samples from the matched non‐infant donors (n = 14, ages 3–63 years). In an observational pilot study of real‐world patients with CLL (n = 12, ages 56–84 years) treated with venetoclax, the plasma M3/venetoclax metabolic ratio negatively correlated with plasma 4β‐HC/cholesterol ratio and positively correlated with patient age. Plasma 4β‐HC/cholesterol ratio negatively correlated with patient age. Differences between the in vitro data, which showed a positive association between venetoclax metabolism, hepatic CYP3A markers, and plasma 4β‐HC/cholesterol ratio, and the in vivo findings in patients with CLL could be due to age or other factors regulating plasma 4β‐HC/cholesterol and/or venetoclax disposition. Future studies with larger sample sizes are needed to investigate age‐related changes in venetoclax metabolism and plasma 4β‐HC/cholesterol ratio.